2019
DOI: 10.1021/acs.est.9b03064
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Primary Emission and Secondary Coating Formation on the Particle Diversity and Mixing State of Black Carbon Particles

Abstract: The mixing state of black carbon (BC) affects its environmental fate and impacts. This work investigates particle diversity and mixing state for refractory BC (rBC) containing particles in an urban environment. The chemical compositions of individual rBC-containing particles were measured, from which a mixing state index and particle diversity were determined. The mixing state index() varied between 26 % and 69% with the average of 48% in this study, and was slightly enhanced with the photochemical age of ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 58 publications
2
24
2
Order By: Relevance
“…Summertime nitrate was low in daytime and high in the nighttime (Fig. 7c), which agrees with measurements at the roadside site in Hong Kong (Lee et al, 2015) and Shanghai (K. . Temperature-dependent gas-particle partitioning would be one of the possible reasons for the observed nitrate diurnal pattern (Appel et al, 1981;Xue et al, 2014;Griffith et al, 2015).…”
Section: The Influence Of Semivolatile Compounds On E Abs Diurnal Varsupporting
confidence: 87%
“…Summertime nitrate was low in daytime and high in the nighttime (Fig. 7c), which agrees with measurements at the roadside site in Hong Kong (Lee et al, 2015) and Shanghai (K. . Temperature-dependent gas-particle partitioning would be one of the possible reasons for the observed nitrate diurnal pattern (Appel et al, 1981;Xue et al, 2014;Griffith et al, 2015).…”
Section: The Influence Of Semivolatile Compounds On E Abs Diurnal Varsupporting
confidence: 87%
“…In contrast, Cappa et al (2012) reported in situ observations of soot absorption enhancement of only 6 % in ambient air. This discrepancy between simulation and observation could be attributed to the complex mixing structure and various morphologies of soot particles in the air (Adachi et al, 2016;Li et al, 2016a;Wu et al, 2018).…”
Section: Introductionmentioning
confidence: 91%
“…As stated by Winkler (1973), “the same net composition of an aerosol can be caused by an infinite variety of different internal distributions of the various compounds.” An “internally mixed” aerosol refers to the state where the composition of all particles within the population is the same (and equal to the bulk composition of the aerosol), while an “externally mixed” aerosol has all particles of a population consisting of only a single species. In reality, aerosol mixing states are between internal and external mixtures as shown in many observational studies (e.g., Bondy et al., 2018; Healy et al., 2014; Lee et al., 2019; Ye et al., 2018; Yu et al., 2020). Aerosol mixing state greatly influences the particles' hygroscopicity (Fierce et al., 2017; Holmgren et al., 2014), their optical properties (Fierce et al., 2016; Lesins et al., 2002), their cloud condensation nuclei (CCN) activity (Ching et al., 2012; Wang et al., 2010), their ice nucleation potential (Knopf et al., 2018), their deposition in the human respiratory system (Ching & Kajino, 2018), and the aerosols' lifetime in the atmosphere (Koch et al., 2009).…”
Section: Introductionmentioning
confidence: 98%
“…In reality, aerosol mixing states are between internal and external mixtures as shown in many observational studies (e.g. Bondy et al, 2018;Healy et al, 2014;Ye et al, 2018; C. Yu et al, 2020;Lee et al, 2019). Aerosol mixing state greatly influences the particles' hygroscopicity (Fierce et al, 2017;Holmgren et al, 2014), their optical properties (Lesins et al, 2002;Fierce et al, 2016), their cloud condensation nuclei (CCN) activity (J.…”
Section: Introductionmentioning
confidence: 99%